2005
DOI: 10.1111/j.1365-2591.2005.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of E. faecalis on the release of serine proteases elastase and cathepsin G, and collagenase‐2 (MMP‐8) by human polymorphonuclear leukocytes (PMNs)

Abstract: The majority of the E. faecalis strains induced little or no release of hydrolytic enzymes from the PMN cells. The finding may partly explain the clinical observation that root canal infections dominated by E. faecalis are usually symptom free.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…Increased levels of several proteolytic enzymes such as elastase, cathepsin G, and MMP-8 released by PMNs in pulpitis and chronic apical periodontitis have been reported (9,10). In this study, TNF-a, IL-1a, and MMP-8 were clearly up-regulated when PMNs were incubated with E. faecalis in vitro (Fig.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Increased levels of several proteolytic enzymes such as elastase, cathepsin G, and MMP-8 released by PMNs in pulpitis and chronic apical periodontitis have been reported (9,10). In this study, TNF-a, IL-1a, and MMP-8 were clearly up-regulated when PMNs were incubated with E. faecalis in vitro (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…The fact remains, however, that E. faecalis is the most common endodontic pathogen in root-filled teeth with persisting infection (3). The possible explanations include that PMNs and E. faecalis live in different environments in failed endodontic cases; they have less opportunity to interact with each other; even in apical area, the inflamed periapical lesion was encapsulated in collagenous connective tissue, which may affect enough PMNs to migrate the perapical lesion and thus may prevent direct PMN phagocytosis; or soluble products of E. faecalis may impair the bactericidal activity of PMNs (10,29,30). When PMNs enter the tissues, they will die within 1 to 2 days, whereas E. faecalis can survive long periods under harsh environmental stress and resuscitate upon returning to more favorable conditions (2).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…faecalis is virulent in chronic periapical lesions because it is resistant to antimicrobial agents such as calcium hydroxide (25). Root canals infected with these bacteria usually remain asymptomatic, with advanced periapical lesions, because they do not respond to conventional endodontic therapy (26). In this study, Endofill, Sealer 26 and Sealapex showed an increase in antimicrobial activity with the addition of AgVO3 against E. faecalis, and AH Plus showed activity that is inherent to the control group, thus these sealers may act as potential agents for the eradication of this microorganism.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of measuring the number of the perfused vessels, which may vary with the change of the cardiac cycle, we used CD31 staining to measure total anatomical blood vessels, which does not change with the change of cardiac cycle. It has been shown that in transverse, but not longitudinal sections of the viable LV wall, capillary density can be an adequate measurement for the number of capillaries per tissue area 33, 34 .…”
Section: Discussionmentioning
confidence: 99%